Students Perception Toward the Importance of Having English Speaking Skill of English Language Education Study Program Universitas PGRI Kalimantan - Zannah*, Fathul; Hidayanti, Desi (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2024)
English is an important international language to master. English is used by various nations to communicate with nations around the world. In order to be able to use English in communication, speaking skills are needed. However, English as a foreign language in Indonesia is a challenge to learn. At school, not many students use it in their daily communication. This needs to be researched and found out how they perceive the importance of having English speaking skills. The objective of this research is to find out and to describe the perception of students of English Language Education Study Program of Universitas PGRI Kalimantan toward the importance of having English speaking skills. This research uses qualitative method. Data were obtained from questionnaire and interview. The subjects of this study were students of third semester as primary data and one of English teacher as secondary data. The number of subjects of this study were thirty six students and one speaking teacher. The process in analyzing the data is done by data reduction, data display, and verification. The results of the analysis show that most students have a positive perception of the importance of having English speaking skills because it has benefits that can be felt in the present is to facilitate students in learning that requires English in the mention and in the future is to facilitate careers after graduating from school, open opportunities to communicate with people from various countries, and increase their value as educated people.